2009
DOI: 10.1128/cvi.00356-08
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Human Immunodeficiency Virus Type 1 Coinfection, Anemia, and Levels and Function of Antibodies to Variant Surface Antigens in Pregnancy-Associated Malaria

Abstract: Human immunodeficiency virus type 1 (HIV-1) coinfection decreases antibodies to variant surface antigens implicated in pregnancy-associated malaria (VSA-PAM) caused by Plasmodium falciparum. The effect of HIV-1 on antibody functions that may protect mothers from pregnancy-associated malaria is unknown. Sera from multigravid pregnant women with malaria and HIV-1 coinfection (n ‫؍‬ 58) or malaria alone (n ‫؍‬ 29) and from HIV-1-infected (n ‫؍‬ 102) or -uninfected (n ‫؍‬ 54) multigravidae without malaria were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 33 publications
(35 reference statements)
4
47
0
Order By: Relevance
“…IgG1 and IgG3 are the predominant antibody isotypes in placental infections (19), indicating that antibodies may opsonize IEs for phagocytosis as well as to inhibit binding. Although inhibitory antibodies have been correlated with protection in some studies (17,25), this correlation has not been observed in all reports, and opsonizing antibodies have also been proposed to have a protective role (28,29,34). It is not known whether women ever achieve sterile immunity against placental infections, but they do acquire a substantial degree of protective immunity after repeated exposure (12).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…IgG1 and IgG3 are the predominant antibody isotypes in placental infections (19), indicating that antibodies may opsonize IEs for phagocytosis as well as to inhibit binding. Although inhibitory antibodies have been correlated with protection in some studies (17,25), this correlation has not been observed in all reports, and opsonizing antibodies have also been proposed to have a protective role (28,29,34). It is not known whether women ever achieve sterile immunity against placental infections, but they do acquire a substantial degree of protective immunity after repeated exposure (12).…”
Section: Discussionmentioning
confidence: 88%
“…Over successive pregnancies, women acquire antibodies to the surface antigens expressed by placental IEs, which correlate with improved pregnancy outcomes (7,25,33,44). Antibodies are thought to protect against placental malaria by inhibiting IE binding to CSA (17,25,40,44) or opsonizing IEs for phagocytosis (28,29,34,52).…”
mentioning
confidence: 99%
“…In sub-Saharan Africa, 25 million pregnant women are currently at risk for malaria, accounting for 10,000 maternal and 200,000 neonatal deaths per year (Matangila et al, 2014;Mbah et al, 2015). In such regions of high transmission and endemicity, sub-clinical malarial infection is common (Takem and D'Alessandro, 2013) and individuals living in such regions usually develop protective immunity to malaria by adolescence; however, this protection is partially abrogated in women during pregnancy, resulting in pregnancy-associated malaria (PAM) (Jaworowski et al, 2009;Takem and D'Alessandro, 2013). Pregnancy-associated malaria results in tremendous obstetrical and paediatric morbidity, including maternal anaemia, intrauterine growth retardation, low birth weight, prematurity, miscarriage, and stillbirth (Tonga et al, 2013;Mbah et al, 2015;White, 2015; Chedraui, Daily and Wylie, 2016; Prahl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These isotypes bind via their Fc domain to Fc␥ receptors, thereby eliciting cellular immune responses of the innate immune system. Antibody opsonization of P. falciparum-infected erythrocytes and merozoites enhances their phagocytosis (6,12,22,30,33,55). The respiratory burst that is elicited by Fc receptor cross-linking furnishes the phagosome with cytotoxic compounds and has been positively associated with protection (20).…”
mentioning
confidence: 99%